LEADERSHIP ROLES IN MOTIVATING VOLUNTEERS IN CIVIC NON-PROFIT ORGANISATIONS : Case: National Coalition party’s Women’s organisation - Sviili, Laura (My University, 2019)
Volunteer organisations and volunteers have an important role locally and internationally in progressing traditional development projects, developing societies and promoting economic development. While the value of volunteering has been recognised widely, traditional long-term volunteering is experiencing changes. Examples of the changes include ad hoc political initiatives such as climate marches or more local initiatives like restaurant days. However, many volunteer organisations still base their activity on regular long-term volunteers. Political parties are a good example of the traditional volunteer organisation, in which the aim is to change society but competing movement form competition from the same volunteers. Volunteers’ motivation and the role of leadership in motivating the volunteers is of particular interest. The study aims to find solutions to maintain long-term volunteer motivation that could be beneficial to the studied local volunteer organisation and to the broader spectrum of NGO’s that base their activities in traditional long-term volunteering. The thesis first examines existing literature on volunteer motivation and volunteer leadership. Thesis utilised Clary et al. (1998) Functional approach on volunteer motivation as the main theoretical model. The research was conducted using qualitative methods since the idea was to gain deep understanding of the studied phenomena. A multiple-case study method was used since the empirical research was conducted to both volunteer leaders and active volunteers in the Women’s organisation of the National Coalition party. Data was collected via semi-structured interviews. Main findings of the study were that main motivators for volunteering within the Women’s organisation were value, understanding and social related aspects. Volunteer leadership within the Women’s organisation is largely based on transformational model of leadership. The contribution to the existing volunteer research is that leaders and volunteers should have a shared value base and teamwork has an important role in volunteering as it helps to progress the goals of the volunteers. Decisions in volunteer organisations should be done together as this makes the volunteers feel that their skills are valued. Volunteers should able to utilise their skills and reach concrete goals by utilising their skills. Lastly it is important that the leaders are able to witness the volunteers’ development, attainment of goals and gaining positive experiences as this makes the leaders themselves experience similar positive emotions.

Vapaaehtoisjärjestöillä ja vapaaehtoisilla on tärkeä tehtävä yhteiskunnallisen ja taloudellisen ke-hityksen edistämisessä paikallisesti ja kansainvälisesti. Vapaaehtoistoiminnan arvo on tunnustettu laajasti, mutta perinteinen pitkäaikaiseen sitoutumiseen perustuva vapaaehtoistyö on muutokses-sa. Tästä hyviä esimerkkejä ovat itsenäiset kansanliikkeet kuten poliittiset ilmastomarssit tai pai-kalliset tapahtumat kuten Ravintolapäivät. Muutoksista huolimatta moni vapaaehtoisjärjestö pe-rustaa edelleen toimintansa säännölliseen pitkäaikaiseen vapaaehtoisuuteen. Tästä hyvä esimerkki ovat poliittiset puolueet, jotka pyrkivät muuttamaan yhteiskuntaa, mutta samalla kilpailevat va-paaehtoisista uusien vapaaehtoisliikkeiden kanssa. Tällaisessa tilanteessa erityinen kiinnostus kohdistuu vapaaehtoisten motivaatioon ja heidän johtamiseensa. Tällä tutkimuksella pyritään löy-tämään keinoja, joilla ylläpidetään pitkäaikaisten vapaaehtoisten motivaatiota niin tutkimuksen kohteena olevissa Kokoomuksen Naisten Liitossa kuin laajemmassa järjestökentässä, jossa keski-tytään perinteiseen vapaaehtoistoimintaan. Tutkielmassa käsiteltiin ensin tutkimuskirjallisuutta vapaaehtoisten motivoimisesta ja johta-misesta. Tutkielman teoreettisena viitekehyksenä oli funktionaalinen lähestymistapa (Clary et al. 1998). Tutkimuksessa käytettiin laadullisia tutkimusmenetelmiä. Tutkimus toteutettiin monita-paustutkimuksena, koska siinä haastateltiin vapaaehtoisia ja piirijohtajia. Tutkimustiedot kerättiin teemahaastatteluilla. Tutkimuksen keskeinen tulos oli, että Kokoomusnaisten vapaaehtoisia motivoivat pääasiassa arvoihin, taitojen kehittämiseen ja sosiaalisiin suhteisiin liittyvät tekijät. Pääasiallinen johtamisen tapa Kokoomusnaisten piirijärjestöissä oli transformationaalinen johtajuus. Tutkimuksen perus-teella voidaan todeta, että vapaaehtoisilla ja heidän johtajillaan tulisi olla yhtenäinen arvopohja. Lisäksi tiimityöskentely on vapaaehtoistoiminnassa tärkeää, sillä sen kautta vapaaehtoiset pysty-vät paremmin edistämään omia tavoitteitaan. Vapaaehtoisten tulisi pystyä saavuttamaan konkreet-tisia tavoitteita niillä taidoilla, joita he omaksuvat vapaaehtoistoiminnassa. On myös tärkeää, että vapaaehtoisten johtajat pystyvät seuraamaan vapaaehtoisten kehittymistä, tavoitteiden saavutta-mista ja myönteisten kokemusten saamista. Tämän kautta johtajat itse saavat samankaltaisia myönteisiä kokemuksia.
Keywords: Volunteering, Volunteer, Leadership, Motivation, Political parties, NGO